Dampak Emoticon dalam Komunikasi di Media Sosial - Shalahuddin, Muhammad Abdurrahman; Fajrianti, Lutfiah (PROPAGANDA, 2024)
This research aims to analyze the impact of emoticons in communication on social media with a focus on their meaning and interpretation and how their use influences the effectiveness of communication. This research was conducted using qualitative methods with a literature study approach which allows collecting and analyzing information from various existing sources. The findings of this research indicate that emoticons can increase the clarity and understanding of messages, enrich the nuances of communication, reduce ambiguity, and provide visual clues about the sender's intentions and emotions, as well as influencing the recipient's perception and response. Emoticons used appropriately can increase the effectiveness of communication and build more personal and empathetic relationships in digital interactions. In addition, emoticons have a positive impact in marketing communications by making messages more interesting and memorable. However, challenges and controversies related to their use are also found, such as variations in the interpretation of emoticons across cultures and contexts, as well as the potential for reducing professionalism in formal communication.